Enhanced Biocide Mitigation of Field Biofilm Consortia by a Mixture of D-Amino Acids - Li, Yingchao; Jia, Ru; Al-Mahamedh, Hussain H.; Xu, Dake; Gu, Tingyue (Frontiers in Microbiology, 2016)
Microbiologically influenced corrosion (MIC) is a major problem in the oil and gas industry as well as many other industries. Current treatment methods rely mostly on pigging and biocide dosing. Biocide resistance is a growing concern. Thus, it is desirable to use biocide enhancers to improve the efficacy of existing biocides. D-amino acids are naturally occurring. Our previous work demonstrated that some D-amino acids are biocide enhancers. Under a biocide stress of 50 ppm (w/w) hydroxymethyl phosphonium sulfate (THPS) biocide, 1 ppm D-tyrosine and 100 ppm D-methionine used separately successfully mitigated the Desulfovibrio vulgaris biofilm on carbon steel coupons. The data reported in this work revealed that 50 ppm of an equimolar mixture of D-methionine, D-tyrosine, D-leucine and D-tryptophan greatly enhanced 50 ppm THPS biocide treatment of two recalcitrant biofilm consortia containing sulfate reducing bacteria(SRB), nitrate reducing bacteria (NRB) and fermentative bacteria, etc. from oil-field operations. The data also indicated that individual D-amino acids were inadequate for the biofilm consortia.